Enzymatic-fluorometric analyses for glutamine, glutamate and free amino groups in protein-free plasma and milk. Issue 1 (2nd March 2017) - Larsen, Torben; Fernández, Carlos
Abstract : This Technical Research Communication describes new analytical methods for free, unbound glutamic acid and glutamine in protein-free blood plasma and milk and introduces the use of quantitation of free amino groups in the same matrices for descriptive and analytical purposes. The present enzymatic-fluorometric methods are easily performed within one working day, allowing for 'high throughput' assays of animal trials. These assays could support and enable further studies in lactation physiology with the objective of improved metabolic health.